2021
DOI: 10.1002/cpe.6655
|View full text |Cite
|
Sign up to set email alerts
|

Target localization in local dense mapping using RGBD SLAM and object detection

Abstract: Summary Target localization in unknown environment is one of the development directions of mobile robots. Simultaneous localization and mapping (SLAM) can be used to build maps in unknown environments, but it has the problem of poor readability and interactivity. In this article, target detection and SLAM are combined to search and locate the target by using rich RGBD images information. The determined position in the global map is conducive to the follow‐up operation of the target by mobile robots. By establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

10
0

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 89 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…The project demonstrates that a trained robot can perform a given task even if it is currently in a state it has never been in before ( Matulis and Harvey, 2021 ). Liu et al proposed a digital-driven machining quality tracking and dynamic control method, which effectively solved the problems of low efficiency of quality problem traceability, poor timeliness and unpredictability of quality control in machining process ( Liu Y et al, 2021b ).…”
Section: Related Workmentioning
confidence: 99%
“…The project demonstrates that a trained robot can perform a given task even if it is currently in a state it has never been in before ( Matulis and Harvey, 2021 ). Liu et al proposed a digital-driven machining quality tracking and dynamic control method, which effectively solved the problems of low efficiency of quality problem traceability, poor timeliness and unpredictability of quality control in machining process ( Liu Y et al, 2021b ).…”
Section: Related Workmentioning
confidence: 99%
“…Good performance of ResNet on image recognition and localization tasks showed that characterisation depth is of central importance for many visual recognition tasks. In the following years, excellent feature extraction networks such as ResNeXt, DenseNet, RegNet, SEnet, SKNet, etc ( Xie et al, 2017 ; Liu X. et al, 2021 ; Liu et al, 2021b ; Liu et al, 2021c ; Liu et al, 2021d ; Sun et al, 2020c ; Sun et al, 2020d ). were successively proposed, constantly refreshing the accuracy rate of tasks such as image classification.…”
Section: Data Analysis and Network Designmentioning
confidence: 99%
“…Position control is the basis and key of the whole underwater navigation control of AUV ( Sun et al, 2020c ; Tao et al, 2021 ; Liu et al, 2022d ). Its position control accuracy is determined by the attitude control accuracy, and the attitude control error of AUV will amplify its position control error, so in order to ensure the high accuracy control of speed and position during underwater navigation, its attitude must be accurately controlled.…”
Section: Auv Attitude Anti-disturbance Decoupling Controlmentioning
confidence: 99%